Pengembangan Ludo Word Game (LWG) Kimia sebagai Media Chemo-Edutainment (CET) pada Materi Sistem Koloid Kelas XI SMA/MA - Dharma Santi Gomulya, Iswendi (Menara Ilmu, 2018)
Chemstry Ludo Word Game (LWG) is one of learning media in games form asexerciese variation for establish the concept of students. The aims of this research todevelope and to determine the validity and practicality level of chemistry LWG asChemo-Edutainment media for Colloids System. The kind of research is Research andDevelopment (R&D) with 4-D models include (1) Define, (2) Design, (3) Develope, and(4) Desseminate. This research was limited on developing of validity and practility ofdeveloping media. This learning media was validated by three lectures of KIMIAFMIPA UNP and two teachers of SMAN 2 Padang Panjang. The practicality leveldetermination was conducted by two teachers of SMAN 2 Padang Panjang and 35students XII MIPA 5 SMAN 2 Padang Panjang. Instrument used in this research arevalidity and practicality questionnaire. The collecting data technique was conducted bydistrubuting the questionnaire and analyzed by Kappa Cohen formula. Data analyzedshow that chemistry LWG as Chemo-Edutainment media for Colloids System has veryhigh validity level and 0.90 as Kappa moment value. The practicality level of this mediais 0,91 categorized very high . The data shows that chemistry LWG as developingChemo-Edutainment media is valid and practice for Colloids System.Keywords: Ludo Word Game (LWG) chemistry, Chemo-Edutainment (CET) media,colloids system, research and development, 4-D models.